153 Prevalence of Low Flow and of Abnormal LV Loading Metrics After Aortic Valve Replacement – A Preliminary Echocardiographic Study. (3rd June 2016) - Gurzun, Magdalena; Mezincescu, Alice; Maskell, Nicholas; Ionescu, Adrian
Abstract : Background: Since the report in 2007 of paradoxical low-flow aortic stenosis (AS) as a distinct entity there has been a lot of interest in low-flow states in patients with AS and preserved LV ejection fraction, their relation with indices of vascular function and in their effect on the conventional metrics used for characterising (AS). Little is known though on the prevalence of low flow and its accompanying vascular functional parameters after successful aortic valve replacement (AVR). Aim of the study and methods: We set out to assess the prevalence of low flow as well as of abnormal valvulo-aortic impedance and systemic arterial compliance following AVR. We recruited unselected, consecutive patients attending our echocardiography laboratory who had interpretable echo images and LF ejection fraction >≥ 50%. We calculated aortic valve area (AVA) by continuity equation; stroke volume indexed to body surface area (SVi = LVOTVTI x LVOTArea ; units -– ml/m 2 ; normal >35 ml/m 2 ) valvulo-aortic impedance Zva = (MPG+SBP)/SVi); units -– mmHg/ml/m 2 ; normal <5 mmHg/ml/m 2 where MPG is mean pressure gradient, SBP is systolic blood pressure and systemic arterial compliance (ml/mm Hg/m 2 ) SAC = SVi/Pulse pressure), normal <≤ 0.6. Results: We studied 77 patients with AVR, 49 male, mean age (SD) 68 (7.8) years. The mean AVA (SD) was 1.59 (0.59) cm 2 ; mean Zva (SD) was 5.02 (0.58); mean SVi (SD) was 30.6 (9.6); mean SAC was 0.48 (0.18). AVA was <1 cm 2 in 11 (14%) patients with AVA, 1–1.5 cm 2 in 24 (32%) and >1.5 cm 2 in 424 (55%). SVi was low in 57 (74%), Zva was elevated in 37 (48%), and SAC was elevated in 16 (21%) of patients. A higher proportion of patients had abnormal SVi, Zva and SAC amongst those with AVA<1.5 cm 2 than in those with AVA >1.5 cm 2 . Conclusion: A significant proportion of patients have abnormal valvulo-aortic loads, low-flow states, and abnormal arterial compliance after successful aortic valve replacement. Further study is warranted to assess the potential clinical significance of these findings.